The wellness activities in the ageing process - Šauerová, Markéta (Acta Salus Vitae, 2013)
The article contemplates the significance of wellness/physical activity in the old age. These acrivities are perceived not only as a factor supporting their independence but also as the way of social isolation prevention and a source of positive emotions.